View from a railroad yard between Huntington Avenue and Boylston Street, ca. 1959 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-northeast from the railroad yard located between Boylston Street to the north-northwest and Huntington Avenue to the south-southeast. The Copley Square Hotel, located at 49 Huntington Avenue, is visible in the center of the photograph. The old Hancock Building, located at 200 Berkeley Street, is visible in the background of the photograph, behind the Copley Square Hotel. Two automobiles are included in the photograph. 7 3/4 x 7 1/2, 9 7/8 x 8 overall Photographs